Adolescent Reproductive Health Promotion for Senior High School Students - Meilani, Niken; Hariadi, Sunarru Samsi; Haryadi, Fransiskus Trisakti (UI Scholars Hub, 2025)
Adolescence is a vulnerable period to reproductive health problems, especially regarding issues of sexuality. Healthy adolescent behavior is needed to achieve the SDGs targets by 2030. This study aimed to analyze personal factors such as attitudes, perceptions, and self-efficacy, as well as environmental factors like family, school, friends, community, and social media's role in adolescent reproductive health behavior and health promotion models. This quantitative analysis was conducted using the survey method with 326 respondents at 32 senior high schools, involving 159 male and 167 female adolescents, as samples taken through a multistage random sampling technique. This study used a questionnaire that was pre-tested for validity and reliability. Data were analyzed using path analysis. The results showed that adolescent perceptions, attitudes, self-efficacy, and the role of parents and social media positively influenced reproductive health behavior. The role of parents is the most influential variable among female adolescents. Social media directly affects male adolescents' behavior and indirectly influences female adolescents. This study recommends integrating social media campaigns with parental involvement to enhance reproductive health literacy. Moreover, health interventions should be sex-specific and consider different ways through which social media influence adolescents.